Методологічні аспекти процесу планування на підприємствах АПК - Сурженко, Нонна Вікторівна; Сурженко, Нонна Викторовна; Surzhenko, Nonna (Мелітополь: Вид-во Мелітопольська типографія «Люкс», 2015)
UK: У статті проведено дослідження методологічних аспектів стратегічного планування. Запропоновано конкретні методи, які можуть ефективно застосовуватись у стратегічному плануванні підприємств АПК. EN: An important part of the strategic planning methodology for agricultural enterprises acting methods, ie specific methods, techniques, with which it is carried out, calculated numerical values of projections of strategic programs and plans. Due to differences on issues of strategic planning using different methods of construction.As established in the study of domestic and foreign literature , the practice planning are three areas: progressive and retrograde circular . The importance of strategic planning classification methods and their purpose distinction scope. The analysis of the scientific literature shows that there are many methods of planning , each author examines several methods.
Keywords: методологія; методика; планування; стратегічне планування; макроекономічна система; ціноутворення; математичне програмування; системний аналіз; methodology; method; planning; strategic planning; macroeconomic framework; pricing; mathematical programming; systems analysis